2001
DOI: 10.1063/1.1287228
|View full text |Cite
|
Sign up to set email alerts
|

Blue photoluminescence in ZnGa2O4 thin-film phosphors

Abstract: The growth and properties of luminescent ZnGa2O4 thin films using pulsed laser ablation has been investigated. As-deposited films on glass and (100) MgO substrates exhibit blue-white photoluminescence with a broad emission band under ultraviolet excitation. In situ epitaxial films obtained on single crystal (100) MgO substrates possess enhanced luminescent intensity as compared to polycrystalline films on glass substrates. The enhanced luminescence in epitaxial films presumably reflects lower defect densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…The structure of ZnGa 2 O 4 is a normal spinel in which the Zn 2+ ions occupy the tetrahedral interstices and the Ga 3+ ions occupy the octahedral interstices [6,7]. It is generally accepted that the intrinsic blue emission of ZnGa 2 O 4 with a peak at 430 nm results from the transition of octahedrally coordinated Ga-O groups [8][9][10]. However, many researchers have observed the blue shift of the emission band from 430 to 360 nm when ZnGa 2 O 4 phosphors are synthesized in a reducing ambient or a zinc deficient environment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of ZnGa 2 O 4 is a normal spinel in which the Zn 2+ ions occupy the tetrahedral interstices and the Ga 3+ ions occupy the octahedral interstices [6,7]. It is generally accepted that the intrinsic blue emission of ZnGa 2 O 4 with a peak at 430 nm results from the transition of octahedrally coordinated Ga-O groups [8][9][10]. However, many researchers have observed the blue shift of the emission band from 430 to 360 nm when ZnGa 2 O 4 phosphors are synthesized in a reducing ambient or a zinc deficient environment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…So, it is deduced that the CL spec- trum of the large-scale nanowires is summation of CL spectra of each single nanowire, and the CL mechanisms of these nanowires are same in nature. Generally, oxygen vacancies and Zn/Ga stoichiometry are the main reasons for the various emission bands of ZnGa 2 O 4 nanowires [20][21][22][23]. Herein, we have demonstrated that the as-prepared ZnGa 2 O 4 nanowires are close to perfect Zn/Ga stoichiometry.…”
Section: Resultsmentioning
confidence: 72%
“…Gallium-indium alloys [2] have demonstrated excellent transmission in the infrared regime, and ZnGa 2 O 4 itself has been identified as a UV-transparent TCO [5,6]. Zincgallate thin films phase have been synthesized to date primarily by sputtering [5], laser ablation [7,8], and sol-gel techniques [9]. There is one report of chemical vapor deposition (CVD) synthesis [10], but we are not aware of attempts to deposit this material by plasma-enhanced chemical vapor deposition (PECVD).…”
Section: Introductionmentioning
confidence: 99%
“…There is one report of chemical vapor deposition (CVD) synthesis [10], but we are not aware of attempts to deposit this material by plasma-enhanced chemical vapor deposition (PECVD). ZnGa 2 O 4 has generated substantial interest lately as a thin film phosphor for electroluminescent devices [7][8][9][10]. Gallium oxide itself has shown potential as a UV transparent TCO [11].…”
Section: Introductionmentioning
confidence: 99%